Metabolic Syndrome; Comparing the Results of Three Definition Criteria in an Iraqi Sample - Al-Azzawi, Omar Farooq (AL-Kindy College Medical Journal, 2018)
Background: Different diagnostic definition and criteria have been recommended by different expert groups for the diagnosis of metabolic syndrome, however, it’s prevalence in the same population could differ depending on the definition used yielding different results. In Iraq, there is a lack of research comparing these different diagnostic definitions. Objective: To find out the most suitable metabolic syndrome definition to be used for Iraqi people. Methods: 320 participants were recruited for this study, 53.4% men and 46.6% women, aged between 25-85 years, visiting Baghdad Teaching Hospital, the prevalence of metabolic syndrome according to different definitions were compared and the agreement was assessed by the Kappa statistic. Results: Metabolic syndrome was diagnosed in 37.8%, 40.6% and 46.9% participants respectively for the National Cholesterol Education Programme Adult Treatment Panel III 2005, International Diabetes Federation 2005 and the recently (2009) revised International Diabetes Federation definition. The prevalence was higher in women than in men, independent of the criteria used. The Kappa statistics suggested that the agreement between the three definitions ranged from good-to-very good, Conclusion: Metabolic syndrome was high in this Iraqi cohort regardless of the definition used. The recently (2009) revised International Diabetes Federation definition may be more suitable in diagnosis of metabolic syndrome in Iraq.